Quantitative And Qualitative Study of Microplastics in Selected Water Bodies of Kochi - Adheena V. S. (Dept.of Aquatic Environment Management., 2017)
Abstract- Plastic is the most prevalent type of marine debris found in our ocean and Great Lakes. Plastic debris can come in all shapes and sizes, but those that are less than five millimeters in length (or about the size of a sesame seed) are called ―microplastics.‖ As an emerging field of study, not a lot is known about microplastics and their impacts yet. Microplastics come from a variety of sources, including from larger plastic debris that degrades into smaller and smaller pieces. In addition, microbeads, a type of microplastic, are very tiny pieces of manufactured polyethylene plastic that are added as exfoliants to health and beauty products, such as some cleansers and toothpastes. These tiny particles easily pass through water filtration systems and end up in the ocean and Great Lakes, posing a potential threat to aquatic life. In India,especially in Kerala, studies related to microplastics distribution are very rare. Hence, we have made an attempt to study the distribution of microplastics from selected areas in Kochi on a monthly basis from January to April in 2017. The river Periyar,the mangrove ecosystem – Mangalavanam,commercially developing areas like Kundannur and Lakeshore (with hospitals and world class hotels nearby) were selected for the study. .Each locations were replicated as two for the comparative study of microplastic pollution and both water and sediment samples were collected from these locations. In this study we have identified and categorized microplastics based on their colour, appearance and chemical forms. Identification of polymer types was done by using FTIR spectroscopy. Microplastics were obtained from every stations with monthly variations. Periyar river showed high values of microplastics in both water as well as sediments with a mean of 4.57±2.29 and 3.857±2.26 respectively. Red coloured fibrous type of microplastics were common in our study . In the Periyar river site, most of the polymers were of Polyamide,Poly Vinyl Chloride and Poly Styrene/Poly EthyleneTerephthalate . The Lakeshore site showed microplastics in water in the range 4.2±3.14 and the Mangalavanam mangrove area showed in the range 3.28±1.7. The Kundannur and Mangalavanam locations showed the presence of polymer types Poly Styrene/Poly Ethylene Terephthalate and for Lakeshore Poly Amide was present along with these polymers. The sampling sites were fixed based on the pollution of the area reported so far and also on the basis of the location of factories and hospitals which are well noted for dumping wastes and other pollutants into the water bodies.